Preparation method of green fluorescent light-emitting diamond

By synthesizing nickel-containing high-nitrogen-type diamonds in high-pressure equipment and performing high-temperature and high-pressure annealing, green fluorescent diamond crystals are prepared, which solves the problems of diamond fluorescent luminescence adjustability and large-size single crystal preparation, and realizes the adjustability and efficient heat dissipation characteristics of various fluorescent effects, which are suitable for multiple application fields.

CN119553348APending Publication Date: 2025-03-04ZHENGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411721062.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

How to grow and achieve the adjustability of diamond fluorescent luminescence, and solve the problem of preparing large-size diamond single crystals with green luminous color centers with different intensities.

Method used

Green fluorescent diamond crystals were prepared by synthesizing nickel-containing high-nitrogen-type diamonds in high-pressure equipment and subjecting high-temperature and high-pressure annealing. The method includes synthesizing diamonds at a pressure of 5.5-6.5 GPa and a temperature of 1300-1600°C, followed by high-temperature and high-pressure annealing at a pressure of 4-7 GPa and a temperature of 1200-2000°C.

Benefits of technology

It realizes green fluorescent luminescence effect of different intensities, and can adjust the fluorescent color and intensity of diamonds by controlling the excitation light source. It is suitable for the production of stage light sources and decorations, and has high-efficiency heat dissipation characteristics. It is suitable for the application of high-power color-center lasers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553348A_ABST
    Figure CN119553348A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a green fluorescent light-emitting diamond, which adopts high-temperature and high-pressure synthesis assembly, and synthesizes a nickel-containing high-nitrogen diamond large single crystal by adding a nitrogen-containing additive in a nickel-containing catalyst system. And carrying out high-temperature and high-pressure annealing assembly, and carrying out high-temperature and high-pressure annealing treatment so as to synthesize the green fluorescent light-emitting large-size diamond single crystal. According to the method, green fluorescent light-emitting diamond single crystals are prepared through secondary treatment of nickel-containing high-nitrogen diamonds synthesized at high temperature and high pressure, green fluorescent light-emitting diamond crystals with different luminous intensities are prepared by regulating and controlling synthesis and annealing conditions, and the green fluorescent light-emitting diamond crystals are expected to be used for special light sources or ornaments on stages, show fluorescent effects of various colors and have broad application prospects. Stage performance dynamic and visual impact is increased; and the application of the diamond in the laser field can be promoted by combining the high-efficiency heat dissipation characteristic of the diamond. The crystal fluorescence luminous intensity of the synthesized diamond single crystal can be dynamically adjusted, the operation is simple, the cost is low, the repeatability is better, and the production requirements can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diamond single crystal growth in crystal growth, and in particular relates to a method for preparing green fluorescent luminous diamond. Background Art

[0002] Diamond fluorescence refers to the phenomenon that diamond emits light when it is excited by external energy. The light emission stops immediately after the excitation source is removed. This phenomenon of light emission is called fluorescence. The unique optical properties of diamond fluorescence show important application value in many fields. First, in the field of biomedicine, diamond can be used as a diagnostic, imaging and therapeutic agent due to its high biocompatibility, low toxicity and excellent fluorescence properties. Secondly, diamond also plays an important role in high-pressure scientific research. The fluorescence effect of diamond anvils affects the Raman scattering spectrum signal-to-noise ratio of the test sample. By studying the fluorescence properties of diamonds, the state of matter under high pressure can be more accurately judged, providing an important basis for scientific research. Finally, diamonds can emit bright green, sky blue, purple, and yellow-green fluorescence under cathode rays, X-rays, and ultraviolet rays, providing innovative light effects and visual effects for stage performances; therefore, diamonds can be used to make special light sources or decorations on the stage. By controlling different excitation light sources, they can show fluorescence effects of various colors, adding dynamics and visual impact to stage performances, and enhancing the overall beauty and sense of technology of the stage.

[0003] Therefore, how to grow and achieve the adjustability of diamond fluorescence is a key scientific and technological issue that needs to be solved in the diamond field. Based on this, conducting research on the regulation of diamond fluorescence is of great significance for realizing the wider application of fluorescent diamonds in science and technology and diamond jewelry. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing green fluorescent diamonds to solve the problem of preparing large-sized diamond single crystals containing green luminescent color centers of different intensities.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing green fluorescent light-emitting diamond comprises the following steps:

[0007] A. Synthesis of nickel-containing high-nitrogen diamond

[0008] A1, sequentially placing a metal steel cap 5, a copper sheet and a carbon sheet 2 in a pyrophyllite container 1, and then placing a composite assembly assembled by a NaCl+ZrO2 sleeve, wherein a graphite heating tube 9 is arranged in the NaCl+ZrO2 sleeve, and an Al2O3+MgO insulating tube is sequentially filled in the interior thereof, and an MgO+ZrO2 column 6 is filled on the insulating tube, a diamond seed crystal 4 and a metal catalyst column are placed in the tube, and a graphite carbon source 7 is placed above the column, and a copper sheet and a carbon sheet 2, and a metal steel cap 5 are sequentially placed in the upper part of the NaCl+ZrO2 sleeve composite assembly to complete the assembly of the synthetic block;

[0009] A2, taking out the synthetic block, using a six-sided top high pressure device at a pressure of 5.5-6.5 GPa and a temperature of 1300-1600°C to synthesize diamond crystals using a 0.2wt.% C3H6N6 additive;

[0010] A3, treating the product obtained in step A2 to remove the metal catalyst on the surface, graphite impurities remaining on the surface of the diamond crystal and other impurities, to obtain a large single crystal of nickel-containing high-nitrogen diamond with a diameter greater than 2 mm;

[0011] B. High-nitrogen diamonds are annealed at high temperature and high pressure to produce green fluorescent diamond crystals

[0012] B1, placing a metal cap 5, a copper sheet and a carbon sheet 2 in a pyrophyllite container 1 in sequence, and then placing a composite assembly assembled by a NaCl+ZrO2 sleeve, wherein a graphite heating tube 9 is arranged in the NaCl+ZrO2 sleeve, and Al2O3+MgO insulating tubes are sequentially filled in the interior thereof, a nickel-containing diamond is placed in the core area of ​​a high-purity graphite powder cavity, and cold-pressed into a graphite column cavity, and the cavity is placed in an Al2O3+MgO insulating tube, and an MgO+ZrO2 column 6 is filled on the insulating tube, and a copper sheet and a carbon sheet 2, and a metal cap 5 are sequentially placed in the upper part of the NaCl+ZrO2 sleeve composite assembly to complete the assembly of the synthetic block;

[0013] B2. Take out the synthetic block and use a six-sided top high pressure equipment to perform high temperature and high pressure annealing treatment on the diamond crystal at a pressure of 4-7 GPa and a temperature of 1200-2000° C. for 5 minutes to several hours;

[0014] B3. The product obtained in step B2 is treated to remove graphite impurities and other impurities remaining on the surface of the diamond crystal to obtain a green fluorescent diamond crystal.

[0015] Further, in step A1, the diamond seed crystal is an industrial diamond of 0.8*0.8 mm, and its {111} face is selected as the seed crystal growth face.

[0016] Furthermore, in step A1, the metal catalyst column is made of iron-nickel alloy.

[0017] Furthermore, in step A1, the graphite carbon source 7 is columnar, and is made by cold pressing after mixing high-purity graphite powder as the carbon source and nitrogen-containing compounds as the carbon source additive.

[0018] Furthermore, in step A1 and step B1, the graphite heating tube 9 has a thickness of 0.9 mm and fits tightly inside the NaCl+ZrO2 casing.

[0019] Furthermore, in step A2 and step B2, before synthesis, the assembled synthesis block is placed in a 120° C. constant temperature oven for drying for two hours.

[0020] Furthermore, in step A2 and step B2, the temperature in the cavity is calibrated using a Pt-30%Rh / Pt-6%Rh double platinum-rhodium thermocouple as a temperature sensing element, and the synthetic pressure is calibrated based on the high-pressure phase transition point of bismuth (Bi), barium (Ba) and thallium (Tl).

[0021] Furthermore, in step A3, the product obtained in step A2 is first placed in hot dilute nitric acid to remove the metal catalyst on the surface, and then placed in a hot mixture of nitric acid and concentrated sulfuric acid to remove graphite impurities remaining on the surface of the diamond crystal; all crystals are ultrasonically cleaned using anhydrous ethanol before testing to remove other impurities on the diamond surface.

[0022] Furthermore, in step B3, the product obtained in step B2 is placed in a hot mixture of nitric acid and concentrated sulfuric acid to remove graphite impurities attached to the surface of the diamond crystal; all crystals are ultrasonically cleaned using anhydrous ethanol before testing to remove other impurities on the diamond surface.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention provides a method for preparing green fluorescent diamonds, which realizes the preparation of large-sized diamond single crystals containing green luminescent color centers of different intensities. The preparation of green fluorescent diamonds of the present invention can not only control different excitation light sources, but also use diamonds as special light sources or decorations on the stage to show fluorescent effects of various colors, add dynamics and visual impact to stage performances, and enhance the overall beauty and technological sense of the stage. Moreover, on the basis of realizing the adjustable green luminescent intensity, the efficient heat dissipation characteristics of diamonds can also be used to promote the application and development of large-sized diamond single crystal materials in high-power color center lasers. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 Diagram of the assembly cavity used to synthesize high-nitrogen diamond;

[0027] Figure 2 Diagram of the chamber assembly for high temperature and high pressure annealing;

[0028] Figure 3 Infrared spectroscopic characterization of diamond after annealing;

[0029] Figure 4 This is a photo of the diamond luminescent under 325nm ultraviolet light after annealing.

[0030] Figure 5a-Figure 5b This is the PL fluorescence excitation spectrum of the diamond crystal after annealing;

[0031] Figure 6 The diamond luminescence comparison is obtained based on the preparation method of green fluorescent diamond in the present invention;

[0032] Figure 7 The figure is a flow chart of the steps of the method for preparing green fluorescent diamond of the present invention.

[0033] In the figure, 1. pyrophyllite container 2. copper sheet and carbon sheet 3. dolomite 4. diamond seed crystal 5. metal steel cap 6. MgO+ZrO2 column 7. graphite carbon source 8. green high nitrogen diamond 9. graphite heating tube 10. graphite column cavity. DETAILED DESCRIPTION

[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention. It should also be noted that, for ease of description, only parts related to the present invention, rather than all structures, are shown in the accompanying drawings.

[0035] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. At the same time, in the description of the present invention, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.

[0036] The method for preparing green fluorescent light-emitting diamond of the present invention comprises the following steps:

[0037] 1. Synthesis of nickel-containing high-nitrogen diamonds. This step is the key basic part of preparing large-sized green fluorescent diamond single crystals.

[0038] In order to prepare green laser crystals later, a catalyst containing nickel metal must be used, and other types of catalysts cannot be used. For this reason, the present invention selects iron-nickel alloy as the metal catalyst.

[0039] In order to grow high nitrogen diamond single crystals, high purity graphite powder (99.9%) is selected as the carbon source, and nitrogen-containing compounds are used as additives of the carbon source. The two are mixed in a certain proportion and then cold pressed into a columnar carbon source. 0.8*0.8mm high-quality industrial diamond is preferably used as the diamond seed crystal, and its {111} face is selected as the seed crystal growth face.

[0040] Assemble the cavity. The assembled cavity is as follows Figure 1 As shown. Specifically, the pyrophyllite container 1 is used as an external container, and the remaining materials will be filled into the container. The metal cap 5, copper sheet and carbon sheet 2 are placed in order, and contact with the composite kit assembled by the NaCl+ZrO2 sleeve to be placed next. First, a layer of graphite heating tube 9 with a thickness of 0.9mm is tightly fitted in the NaCl+ZrO2 sleeve, and the MgO+ZrO2 column 6 (magnesium oxide + zirconium oxide plug) and Al2O3+MgO insulating tube are filled in it in turn; the seed crystal and metal catalyst column are placed in the Al2O3+MgO insulating tube, which is the position for the growth of diamond samples, and the graphite carbon source 7 is placed above it, which can just seal the insulating tube; the MgO+ZrO2 column 6 is filled on the Al2O3+MgO insulating tube, which just seals the NaCl+ZrO2 sleeve tightly. Similarly, the copper sheet and carbon sheet 2, and the metal cap 5 need to be placed in the upper part of the NaCl+ZrO2 sleeve composite assembly.

[0041] Before the synthesis experiment, in order to remove the adsorbed water in the synthesis block, the assembled synthesis block was placed in a 120°C constant temperature box for two hours to dry; then the synthesis block was taken out for diamond synthesis experiment under the six-sided top high pressure equipment, and the synthesis experiment of diamond crystal was carried out using a pressure of 5.5-6.5GPa and a temperature of 1300-1600°C, and a 0.2wt.% C3H6N6 additive was used to synthesize nickel-containing high nitrogen diamond crystals. The temperature in the cavity was calibrated using a Pt-30%Rh / Pt-6%Rh double platinum-rhodium thermocouple as a temperature sensing element, and the measurement error was less than 5%. The synthesis pressure was calibrated based on the high pressure phase transition points of bismuth (Bi), barium (Ba) and thallium (Tl). After the experiment, the experimental product was first placed in hot dilute nitric acid to remove the metal catalyst on the surface, and then placed in a hot mixture of nitric acid and concentrated sulfuric acid to remove the graphite impurities remaining on the surface of the diamond crystal. All crystals were ultrasonically cleaned with anhydrous ethanol before testing to remove other impurities on the surface of the diamond, ultimately obtaining large single crystals of nickel-containing, high-nitrogen diamond with a diameter greater than 2 mm.

[0042] 2. Perform high-temperature and high-pressure annealing on high-nitrogen diamonds to prepare green fluorescent diamond crystals. This part is the core step of high-pressure treatment.

[0043] Based on the preparation of high-nitrogen diamond single crystals by nickel-based catalyst in step 1, the obtained diamond crystals need to be further treated for a second time. The diamond synthesis experiment under the same synthesis parameters in step 1 is repeated many times to obtain multiple nickel-containing high-nitrogen diamonds. Specifically, high-temperature and high-pressure annealing assembly is used to perform high-temperature and high-pressure annealing treatment on the crystals synthesized in step 1.

[0044] The present invention selects high-purity graphite powder (99.9%) as the graphite core cavity during annealing of high-nitrogen diamond single crystal. The assembled cavity is as follows Figure 2 As shown. Specifically, the pyrophyllite container 1 is used as an external container, and the remaining materials will be filled into the container. The metal cap 5, copper sheet and carbon sheet 2 are placed in order, and contact with the composite kit assembled by the NaCl+ZrO2 sleeve to be placed next. First, a layer of graphite heating tube 9 with a thickness of 0.9mm is tightly fitted in the NaCl+ZrO2 sleeve, and the MgO+ZrO column 6 and Al2O3+MgO insulating tube are filled in turn; the nickel-containing diamond is placed in the core area of ​​the high-purity graphite powder cavity, and cold-pressed into a graphite column cavity, and the cavity is placed in the Al2O3+MgO insulating tube as a position for uniform heat annealing of the diamond sample; the MgO+ZrO column 6 is filled on the Al2O3+MgO insulating tube, just to tightly seal the NaCl+ZrO2 sleeve. Similarly, the carbon sheet and copper sheet 2, and the metal cap 5 need to be placed in the upper part of the NaCl+ZrO2 sleeve composite assembly.

[0045] Similarly, before the synthesis experiment, the assembled synthesis block was placed in a 120°C constant temperature box for two hours to remove the bound water in the assembly block; the assembly block was then taken out for diamond high temperature and high pressure annealing treatment under the six-sided top high pressure equipment, and the high temperature and high pressure annealing treatment experiment of the diamond crystal was carried out for 5 minutes to several hours using a pressure of 4-7GPa and a temperature of 1200-2000°C. The temperature in the cavity was calibrated using a Pt-30%Rh / Pt-6%Rh double platinum-rhodium thermocouple as a temperature sensing element, with a measurement error of less than 5%, and the synthesis pressure was calibrated based on the high pressure phase transition points of bismuth (Bi), barium (Ba) and thallium (Tl).

[0046] After the experiment, the experimental product was added to a hot mixture of nitric acid and concentrated sulfuric acid to remove graphite impurities attached to the surface of the diamond crystal. All crystals were ultrasonically cleaned with anhydrous ethanol before testing to remove other impurities on the diamond surface, and finally a large single crystal of nickel-containing high-nitrogen diamond was obtained after high temperature and high pressure annealing. The crystals after high temperature and high pressure annealing were experimentally measured and characterized, and infrared spectroscopy was performed using a BRUKER VERTEX 70V Fourier transform infrared spectrometer (FTIR) with a spectral range of 400cm -1 -4000cm -1 , the spectral resolution is 2cm -1 , the test mode is selected as transmission. Leica optical photos are collected using a Leica M205c optical microscope (OM) under ultraviolet light, and the PL fluorescence excitation spectrum of the diamond crystal after annealing is measured using a HORIBA Fluorolog-3 fluorescence spectrometer. The excitation laser sources are selected as 325nm and 430nm respectively.

[0047] Figure 3 This is the infrared spectrum characterization of diamond. As shown in the figure, curves (F-1) to (F-6) correspond to Figure 4 Crystal (1) - Crystal (6). Through the analysis of the curve obtained by infrared spectroscopy, it can be seen that the nitrogen content of the diamond crystal is between 880-1100ppm, which can be said to be a typical high-nitrogen diamond crystal. Figure 3 The middle curve (F-1) corresponds to the nickel-containing high-nitrogen crystal that has not been annealed at high temperature and high pressure. Figure 3 The middle curve (F-2) to the curve (F-6) are high nitrogen crystals after high temperature and high pressure annealing. It can be clearly seen from the infrared curve that the effect of high temperature and high pressure annealing, that is, after high temperature and high pressure annealing, the nitrogen atoms in the crystal exist in the form of C center (located at 1130cm) before annealing. -1 ) and transformed into the A center in the form of atomic pairs (located at 1282cm -1 This is a typical feature of high temperature and high pressure annealing treatment.

[0048] like Figure 4 The following are photos of diamond luminescence under ultraviolet light (325nm). Crystals (1) to (6) correspond to diamond crystals with different luminescence intensities. The obtained crystals were characterized. First, using ultraviolet light excitation, it can be seen that Figure 4 The crystal (1) is a diamond crystal that has not been subjected to high temperature and high pressure annealing treatment. At this time, the crystal does not have the characteristic of green fluorescence. In the figure, crystals (2) to (6) are crystals obtained after high temperature and high pressure treatment. It can be seen that the luminescence of the crystals is different, which also shows that the present invention can achieve the preparation of green laser diamonds with different luminescence intensities through high temperature and high pressure annealing treatment.

[0049] Figure 5a , Figure 5b These are the PL fluorescence excitation spectra of the crystal under 325nm and 430nm laser sources. Figure 5a , Figure 5b As shown, the characterization results of the PL fluorescence excitation spectrum are also confirmed by the results of the green fluorescence luminescence of the crystal. The PL results show that only the crystals prepared by high temperature and high pressure treatment will have a strong luminescence peak at about 530nm, corresponding to the green light band.

[0050] Figure 6 The comparison results of the diamond crystal synthesized by the present invention before and after being processed into diamond jewelry. The two pictures on the left are the colors of the processed diamonds under normal white light, and the two pictures on the right correspond to the crystals producing green fluorescence under ultraviolet light. From the results, it can be seen that the crystals synthesized by us can completely achieve green fluorescence under ultraviolet light after being processed into diamonds, so it can be fully applied in the fields of stage decoration, lighting, etc.

[0051] Figure 7 The present invention is a flow chart of the steps of preparing green fluorescent diamonds. The method mainly includes the following steps: First, using high-pressure synthesis assembly, diamonds with different nitrogen contents are synthesized at a pressure of 5.5-6.5 GPa and a temperature of 1300-1600°C. Then, the synthesized diamonds are placed in a high-pressure annealing assembly and subjected to high-pressure annealing treatment at a pressure of 4.0-7.0 GPa and a temperature of 1200-2000°C. Finally, the treated diamonds are processed to obtain green fluorescent diamonds that can be used in the field of diamond jewelry.

[0052] Example 1

[0053] For the nickel-containing high-nitrogen diamond crystal synthesized at a pressure of 5.8 GPa and a temperature of 1350°C using a 0.2 wt.% C3H6N6 additive, a high-temperature high-pressure annealing treatment was performed at a pressure of 5 GPa and a temperature of 1750°C for 25 minutes. The resulting fluorescent diamond crystal is as follows: Figure 4 The crystal (3) is shown in FIG.

[0054] Example 2

[0055] For the nickel-containing high-nitrogen diamond crystal synthesized with 0.2wt.% C3H6N6 additive at a pressure of 5.8GPa and a temperature of 1350°C, a high-temperature high-pressure annealing treatment was performed at a pressure of 5GPa and a temperature of 1700°C for 30 minutes. The obtained fluorescent diamond crystal is as follows Figure 4 The crystal (5) is shown in FIG.

[0056] Example 3

[0057] For the nickel-containing high-nitrogen diamond crystal synthesized by 0.2wt.% C3H6N6 additive at a pressure of 5.8GPa and a temperature of 1350°C, without high temperature and high pressure annealing treatment, the fluorescence luminescence of the obtained diamond crystal is as follows Figure 4 The crystal (1) is shown in FIG.

[0058] The remaining embodiments (Example 4-Example 19) are given in the form of a table below:

[0059]

[0060] It can be seen from the above embodiments that the high nitrogen diamond without annealing does not show fluorescence behavior; when the high nitrogen diamond synthesized by high temperature and high pressure is subjected to high temperature and high pressure annealing, it shows obvious fluorescence behavior. The fluorescence phenomenon has obvious regular changes with the synthesis temperature and annealing temperature of the diamond. Specifically, the synthesis conditions used for synthetic diamonds are not suitable. When they are too high or too low, it is not conducive to the fluorescence phenomenon of diamonds. 5.8GPa and 1350℃ are suitable synthesis conditions; when the diamond is subjected to high temperature and high pressure annealing, the annealing conditions used are not suitable (too high or too low), which will significantly affect the fluorescence intensity of the diamond. 5GPa and 1650-1750℃ are suitable annealing conditions. When using C3H6N6 as an additive to synthesize high nitrogen diamonds, this is not used as a limitation. The doping ratio that can normally synthesize high-quality high nitrogen diamond crystals is suitable, for example, 0wt.%-0.3wt.%.

[0061] Note that the above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention has been described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for preparing green fluorescent diamond, characterized in that: The following steps are involved: A. Synthesis of nickel-containing high-nitrogen diamond A1. Place a metal steel cap (5), a copper sheet and a carbon sheet (2) in a pyrophyllite container (1) in sequence, and then place a composite assembly assembled with a NaCl+ZrO2 casing. A graphite heating tube (9) is arranged in the NaCl+ZrO2 casing, and an Al2O3+MgO insulating tube is filled in the interior of the casing in sequence. An MgO+ZrO2 column (6) is filled on the insulating tube. A diamond seed crystal (4) and a metal catalyst column are placed in the tube, and a graphite carbon source (7) is placed above the column. A copper sheet and a carbon sheet (2) and a metal steel cap (5) are placed in sequence on the upper part of the NaCl+ZrO2 casing composite assembly to complete the assembly of the synthesis block. A2, taking out the synthetic block, using a six-sided top high pressure device at a pressure of 5.5-6.5 GPa and a temperature of 1300-1600°C to synthesize diamond crystals using a 0.2wt.% C3H6N6 additive; A3, treating the product obtained in step A2 to remove the metal catalyst on the surface, graphite impurities remaining on the surface of the diamond crystal and other impurities, to obtain a large single crystal of nickel-containing high-nitrogen diamond with a diameter greater than 2 mm; B. High-nitrogen diamonds are annealed at high temperature and high pressure to produce green fluorescent diamond crystals B1, placing a metal rigid cap (5), a copper sheet and a carbon sheet (2) in a pyrophyllite container (1) in sequence, and then placing a composite assembly assembled with a NaCl+ZrO2 casing, wherein a graphite heating tube (9) is arranged in the NaCl+ZrO2 casing, and Al2O3+MgO insulating tubes are sequentially filled in the interior thereof, a nickel-containing diamond is placed in the core area of ​​a high-purity graphite powder cavity, and cold-pressed into a graphite column cavity, and the cavity is placed in an Al2O3+MgO insulating tube, and an MgO+ZrO2 column 6 is filled on the insulating tube, and a copper sheet and a carbon sheet (2) and a metal rigid cap (5) are sequentially placed in the upper part of the NaCl+ZrO2 casing composite assembly to complete the assembly of the synthetic block; B2. Take out the synthetic block and use a six-sided top high pressure equipment to perform high temperature and high pressure annealing treatment on the diamond crystal at a pressure of 4-7 GPa and a temperature of 1200-2000° C. for 5 minutes to several hours; B3. The product obtained in step B2 is treated to remove graphite impurities and other impurities remaining on the surface of the diamond crystal to obtain a green fluorescent diamond crystal.

2. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: Step A1, the diamond seed crystal is an industrial diamond of 0.8*0.8 mm, and its {111} face is selected as the seed crystal growth face.

3. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: In step A1, the metal catalyst column is made of iron-nickel alloy.

4. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: Step A1, the graphite carbon source (7) is in a columnar shape, and is made of high-purity graphite powder as a carbon source, a nitrogen-containing compound as an additive of the carbon source, and the carbon source and the carbon source additive are mixed and then cold-pressed.

5. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: In step A1 and step B1, the graphite heating tube (9) has a thickness of 0.9 mm and fits tightly inside the NaCl+ZrO2 casing.

6. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: In step A2 and step B2, before synthesis, the assembled synthesis block is placed in a 120° C. constant temperature oven for drying for two hours.

7. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: In step A2 and step B2, the temperature in the cavity is calibrated using a Pt-30%Rh / Pt-6%Rh double platinum-rhodium thermocouple as a temperature sensing element, and the synthetic pressure is calibrated based on the high-pressure phase transition point of bismuth, barium and thallium.

8. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: In step A3, the product obtained in step A2 is first placed in hot dilute nitric acid to remove the metal catalyst on the surface, and then placed in a hot mixture of nitric acid and concentrated sulfuric acid to remove graphite impurities remaining on the surface of the diamond crystal; all crystals are ultrasonically cleaned with anhydrous ethanol before testing to remove other impurities on the diamond surface.

9. The method for preparing a green fluorescent diamond according to claim 1, characterized in that: In step B3, the product obtained in step B2 is placed in a hot mixture of nitric acid and concentrated sulfuric acid to remove graphite impurities attached to the surface of the diamond crystal; all crystals are ultrasonically cleaned with anhydrous ethanol before testing to remove other impurities on the diamond surface.

Citation Information

Patent Citations

  • Method to produce light-emitting nano-particles of diamond

    CN101679040A

  • Preparation and application of high-coherence diamond nitrogen cavity and diamond anvil cell

    CN114941173A

  • Method of producing fluorescent diamond particles

    US20210371741A1